Pemanfaatan Digital Marketing Sebagai Sarana Pemasaran UMKM Taso Ndeso Di Kelurahan Sukorejo Kota Blitar - Annisa Aprilia Husnul Khotimah; Danurwenda Permana Erlushandy; Virginia Mandasari (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Digital marketing is a marketing activity or promotion of goods or brands using digital media or the internet to quickly attract consumers or potential customers. The method used in this study is a qualitative method. This research focuses on Taso Ndeso MSMEs located in RT 4 RW 12 Sukorejo Village, Blitar City. This is because the Taso Ndeso MSMEs themselves still have not utilized and have not used marketing through digital marketing to promote their products. Digital marketing utilization has becoming the important key of MSMEs “Taso Ndeso” in Sukorejo Village, Blitar City in attempt of increasing their market. By using digital platform like social media and website, MSMEs could reach better market outside their region. By showing their unique and nice products. MSMEs “Taso Ndeso” could attract potential consumer attention and increase their visibility. One of their digital marketing benefit for MSMEs “Taso Ndeso” are their capability for live interaction with customer. By using comment, direct message, and online survey, MSMEs could get precious feedback and understanding what their customer preference and also what their customer needed. By this knowledge MSMEs could fix and increase their products like what their customer needed, make them more competitive in market. Beside of that, digital marketing also have an important role to build great products for MSMEs “Taso Ndeso”. By using interesting visual content and story telling that can build emotions whos watching. MSMEs could convey their value and their unique products to audiens. By differentiate themself from competitor and build strong relationship with their customer. MSMEs “Taso Ndeso” can make their strong identity and their customer trust with their products in long term.